The two-way link between eating behavior and brain metabolism - Tanya Zilberter (Frontiers Research Topics, 2016)
This research topic collected and connected information concerning both the underlying metabolic mechanisms and consequences of eating behaviors. These two aspects are tremendously important for a better understanding of eating behavior abnormalities as well as for improving education on eating disorders and behaviors.